Measuring Financial Health of E.I.D. Parry Sugar Limited Using ’Z’ Score Model - A Case Study - Suriyamurthi, S.; Velavan, M. (Indian Journal of Finance, 2010)
Going global, Survival of the business in the modern world is the driving force to do better than others. In order to survive, and continue to be in business, it is essential that an organization successfully manages its finance, which requires more attention and care. Ineffective management is one of the important factors causing industrial sickness. Many variables are available to indicate the business sickness. Therefore, it is important to monitor the financial position and health of company through its financial statements, which throws light on the operational efficiency and financial position of the company. The principle objective of this article is to ascertain the financial health of EID Parry Sugars Limited Company and consistency of financial performance for ten years from 1998-99 to 2007-08. The research findings are that the company maintains good financial performance / health throughout the study period.